Draft Genome Sequences of Streptomyces sp. Strains MH60 and 111WW2 - Thatcher, Louise F. (Genome Announc, 2018)
We report here the draft genome sequences, annotations, and predictions of secondary metabolite gene clusters of two endophytic Streptomyces species isolated from wheat plants growing in the Western Australian wheat belt. These strains, Streptomyces sp. strains MH60 and 111WW2, possess antifungal and/or plant growth-promoting activities.